2017
DOI: 10.1111/jen.12377
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota field population of western corn rootworm (Coleoptera: Chrysomelidae) shows incomplete resistance to Cry34Ab1/Cry35Ab1 and Cry3Bb1

Abstract: In the United States of America, the western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), is commonly managed with transgenic corn (Zea mays L.) expressing insecticidal proteins from the bacteria Bacillus thuringiensis Berliner (Bt). Colonies of this pest have been selected in the laboratory on each commercially available transformation event and several resistant field populations have also been identified; some field populations are also resistant. In this study, progeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 34 publications
4
82
1
Order By: Relevance
“…In cases where Cry34/35Ab1 resistance was found in this study, resistance ratios ranged from 9 to 19 (see Results), suggesting that the level of resistance found in the field has increased over time. Furthermore, one of the problem field populations (PF2) showed complete resistance to Cry34/35Ab1 maize, while past studies had only found incomplete resistance . This increase in resistance observed in the present study, compared to past studies, parallels results for western corn rootworm resistance to Cry3Bb1 maize, where resistance to Cry3Bb1 maize increased significantly over time for western corn rootworm populations from fields associated with high levels of feeding injury to Cry3Bb1 maize …”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In cases where Cry34/35Ab1 resistance was found in this study, resistance ratios ranged from 9 to 19 (see Results), suggesting that the level of resistance found in the field has increased over time. Furthermore, one of the problem field populations (PF2) showed complete resistance to Cry34/35Ab1 maize, while past studies had only found incomplete resistance . This increase in resistance observed in the present study, compared to past studies, parallels results for western corn rootworm resistance to Cry3Bb1 maize, where resistance to Cry3Bb1 maize increased significantly over time for western corn rootworm populations from fields associated with high levels of feeding injury to Cry3Bb1 maize …”
Section: Discussionsupporting
confidence: 73%
“…Bt maize producing Cry34/35Ab1 was registered by the US EPA in 2005 and the first evidence of resistance was found in 2013 from fields in Iowa and Minnesota where high levels of feeding injury were observed for maize containing Cry34/35Ab1 . The results reported here indicate additional cases of resistance to Cry34/35Ab1 within the agricultural landscape.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In Iowa, western corn rootworm with field‐evolved resistance to Cry34/35Ab1 and eCry3.1Ab also has been identified (Gassmann et al., ; Jakka, Shrestha, & Gassmann, ). Additionally, resistance to various Cry proteins has been reported from Nebraska (Wangila, Gassmann, Petzold‐Maxwell, French, & Meinke, ), Illinois (Schrader, Estes, Tinsley, Gassmann, & Gray, ) and Minnesota (Ludwick et al., ; Zukoff et al., ). Jakka et al.…”
Section: Introductionmentioning
confidence: 99%